Intended and unintended consequences: Ethics, communication, and prognostic disclosure in pediatric oncology. Issue 6 (26th December 2017) - Marron, Jonathan M.; Cronin, Angel M.; Kang, Tammy I.; Mack, Jennifer W.
Abstract : BACKGROUND: The majority of patients desire all available prognostic information, but some physicians hesitate to discuss prognosis. The objective of the current study was to examine outcomes of prognostic disclosure among the parents of children with cancer. METHODS: The authors surveyed 353 parents of children with newly diagnosed cancer at 2 tertiary cancer centers, and each child's oncologist. Using multivariable logistic regression, the authors assessed associations between parental report of elements of prognosis discussions with the oncologist (quality of information/communication and prognostic disclosure) and potential consequences of these discussions (trust, hope, peace of mind, prognostic understanding, depression, and anxiety). Analyses were stratified by oncologist‐reported prognosis. RESULTS: Prognostic disclosure was not found to be associated with increased parental anxiety, depression, or decreased hope. Among the parents of children with less favorable prognoses (<75% chance of cure), the receipt of high‐quality information from the oncologist was associated with greater peace of mind (odds ratio [OR], 5.23; 95% confidence interval [95% CI], 1.81‐15.16) and communication‐related hope (OR, 2.54; 95% CI, 1.00‐6.40). High‐quality oncologist communication style was associated with greater trust in the physician (OR, 2.45; 95% CI, 1.09‐5.48) and hope (OR, 3.01; 95% CI, 1.26‐7.19). Accurate prognostic understanding was less common among the parents of children with less favorable prognoses (OR, 0.39; 95% CI, 0.17‐0.88). Receipt of high‐quality information, high‐quality communication, and prognostic disclosure were not found to be significantly associated with more accurate prognostic understanding. CONCLUSIONS: The results of the current study demonstrate no evidence that disclosure is associated with anxiety, depression, or decreased hope. Communication processes may increase peace of mind, trust, and hope. It remains unclear how best to enhance prognostic understanding. Cancer 2018;124:1232‐41. © 2017 American Cancer Society . Abstract : In this examination of the role of prognostic disclosure in pediatric oncology, the authors report no evidence that disclosure is associated with increased parental anxiety or depression or with decreased hope. Instead, communication processes may increase peace of mind, trust, and hope, although it remains unclear how best to bridge the gap between prognostic disclosure and prognostic understanding.